Implementation of Rahn in Islamic Financial Institutions in Indonesia: Operational, Economic, and Regulatory Analysis - Nur Sania Dasopang; Adli Siregar (Islamic Circle, 2026)
This study aims to analyse the implementation of the rahn contract in Islamic financial institutions in Indonesia, with a focus on operational mechanisms, economic benefits and regulatory challenges. This study employs a qualitative-descriptive approach using a literature review method, examining primary data comprising Islamic banking regulations, DSN-MUI fatwas, and Sharia principles, as well as secondary data from OJK reports, academic journals, and publications by Islamic financial institutions. The research findings indicate that the rahn contract is an Islamic financial instrument that enables customers to obtain qardh-based loans by pledging movable assets as collateral, whilst the institution receives ujrah as remuneration for storage services. The operational mechanisms implemented at Pegadaian Syariah and Islamic banks are in line with Sharia principles, particularly regarding the separation of loan value and service fees. Economically, rahn makes a significant contribution to enhancing financial inclusion, particularly for low-income communities requiring quick and secure access to funds. However, this study also identified several regulatory challenges, such as inconsistencies between regulations from the OJK, BI, and DSN fatwas, low public literacy regarding rahn, as well as operational risks such as moral hazard and inaccurate asset valuation. This study underscores the need to strengthen policies and standardise mechanisms so that the implementation of rahn contracts becomes more effective and provides added value for the development of Islamic finance in Indonesia